OBSERVATION OF CHILDREN EXPERIENCED MENINGOCOCCAL INFECTION - O.A. Rychkova; E.A. Kashuba; T.G. Drozdova; A.A. Bel'tikova ("Paediatrician" Publishers LLC, 2010)
(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):156-157)